PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH BANK SYARIAH TANGGAMUS - Meiria Nurphi; Dedi Wahyudi (Jurnal Signaling, 2021)
Increasing public awareness of the practice of Islamic values in economic activities is one of the reasons behind the development of Islamic financial institutions in Indonesia, one of which is improving the quality of services. Companies are required to try to make customers feel satisfied by providing better offers and services, considering that the company must be able to maintain its market position in the midst of increasingly fierce competition. In this study, the regression coefficient of service quality variable (X) was 0.193, which means that service quality has a positive effect on customer satisfaction of 19.3%, this proves that Tanggamus Syariah Bank must pay attention to the quality of services provided to its customers.